The Impact of Tax Literacy, Financial Condition on Tax Compliance With Tax Awareness as a Moderating Variable - Khofifah, Nur; Hariyanto, Dedi (Trunojoyo University of Madura, 2024)
This study implements an associative research design with the goal of discovering the nature of the relationship that exists between Tax Literacy Factors (X1), Financial Situation (X2), and Individual Taxpayer Compliance (Y), with Taxpayer Awareness serving as a moderating variable (Z). Data was collected using questionnaires with a rating system called Likert that included five potential replies. Google Forms is utilized to ease the participant collection procedure. The study's population comprised people who completed questions using Google Forms. A variety of data analysis procedures are employed to investigate the obtained data. These processes include validity and reliability testing, classical assumption tests, linear regression and MRA, determination coefficient tests, simultaneous F tests, and partial T tests. According to the determination test, the variables included in this study accounted for 99.5% of the variance, with the remaining 5% affected by unspecified factors. This study's concurrent findings reveal that tax literacy and financial situation have a considerable impact on individual taxpayer compliance, and taxpayer awareness can attenuate the effects of tax literacy factors and financial condition on oribadi taxpayer compliance in Pontianak. The data management technique is carried out utilizing IBM SPSS 26